Chronic Constipation: Current Management and Challenges - Martin Storr (Canadian Journal of Gastroenterology)
Many challenges are associated with the diagnosis and management of patients with chronic constipation. Some of these challenges arise from the currently incomplete understanding of what causes constipation and from the difficulties in diagnosing and classifying the heterogeneous group of patients with chronic constipation. Despite the availability of different treatment options for constipation, an unmet need for drugs in the treatment of patients with chronic constipation remains. This holds especially true for patients who fail an initial treatment. With promising novel drugs either close to approval for the Canadian market or on the horizon, many of these unmet needs may be addressed. The present supplement to The Canadian Journal of Gastroenterology provides an educational overview of the current understanding of the diagnosis, epidemiology, pathophysiology and management of chronic constipation, and summarizes current treatment options in light of current and newly available drugs.